Prevalence of Viral Hepatitis Among Pregnant Women Attending Traditional Birth Homes in Southern Nigeria - Utibe-Abasi O. Alfred, Euphoria C. Akwiwu *, Valerie E. Ugochi, Josephine O. Akpotuzor (Sokoto Journal of Medical Laboratory Science)
Despite emerging infections and diseases that are transmissible through poor gynaecology/ obstetrics care, preference for traditional birth attendants over conventional caregivers still exist. Laboratory diagnosis remains essential for detection of new cases as well as overall management of infected persons. Pregnant women accessing care at traditional birth homes constitute a vulnerable group since laboratory testing for hepatitis is lacking at the centers, hence the present study. This study employed a descriptive cross-sectional study design. The study participants were pregnant women accessing care at traditional birth homes in Uyo, Akwa Ibom State of Nigeria. The subjects were each screened for the presence of antibodies to HBV and HCV using immunochromatographic methods. Data processing was carried out using SPSS version 22.0. Results are presented as numbers and frequencies expressed as percentages. Socio-economic variables including education and income were seen to be disproportionally distributed among the pregnant women accessing care at traditional birth homes. Five (5) out of 88 enrolled pregnant women were reactive to either of both viral hepatitis screened. The prevalence of HBV (4.5%) was higher than that of HCV (1.1%). Six out of the seven (85.7%) centers informed the attendees of the need to undertake laboratory screening for transmissible infections. However, none of the centers made it mandatory for laboratory test results to be obtained. One center out of seven (14.3%) ensured that sharps used during child delivery were not shared. This study observed the prevalence of hepatitis B and C virus infections among pregnant women attending traditional birth homes in Uyo, Nigeria to be 4.5% and 1.1% respectively.